THE EFFECT OF BRAINSTORMING ON EFL READING COMPREHENSION - Yen, Tran Thi Ngoc (VNU Journal of Foreign Studies, 2017)
This study investigates the effect of brainstorming techniques on EFL learners’ reading comprehension. The experiment in this study involved a treatment group and a control group, both of which were following an English course at a language centre in Vietnam. The treatment group were trained in brainstorming techniques during reading lessons whereas the control group were not. Comparisons between the two groups’ average scores on pre-test and post-test and their comprehension improvement during the course showed that the treatment group outperformed the control group and thus confirmed that brainstorming has a positive impact on EFL reading comprehension.